Gambaran Histologi Ginjal Tikus Wistar Yang Terpapar MSG Setelah Perlakuan Diberikan Jus Tomat Dan Diberhentikan Perlakuan Saja - Yeti Eka Sispitasari (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2018)
MSG causes many side effects on the body, but MSG has long been used as a food flavor that can bring tastes (umami) and play a role in strengthening the taste. The chemical structure of MSG is no different from Glutamic Acid (glutamate), it is one of the 20 amino acids that make up proteins in the body. So the use of MSG needs to be discontinued to prevent kidney damage due to continued consumption of MSG, two research were conducted to determine the effect of discharging of MSG consumption by being given tomato juice (1) and discharged without treatment (2), the second study was seen from the histology picture of rats wistar mouse.Methods were experimental with post test only control group design. The research (1) used 15 wistar rats divided into three groups: group I without treatment (pellet AD II and drinking water), group II was given MSG for 14 days and group III was given tomato juice and MSG for 14 days. The study (2) used 27 rats divided by 9 groups. The sample is selected by simple random sampling method. The mice were then gradually turned off on the 29th, 43rd and 57th days. There was no significant difference in mean number of normal and damaged proximal tubules in all treatment groups. The renal histologic features in the treatment group I (MSG) and the treatment group II (MSG and tomato juice) showed normal glomeruli, tubular epithelial tubules, and lumen tubular narrowing whereas in mice discharged without treatment there was no apparent difference between the two MSG Giving groups damage to proximal tubules and renal corpusculum and regeneration after 14 days of discontinuation of MSG. Conclusions from these two experiments occurred damage to the renal tubules Keywords: MSG, Kidney, Wistar Rat